Analisis Antara Interaksi Sosial Dan Perkembangan Bahasa Anak Usia Dini di Tk Negeri Adenium - Amalia Putri Monoarfa; Amelia Daaliwa; Cindawati Pakaya; Pratiwi Monoarfa; Pupung Puspa Ardini (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The development of the Indonesian language is very important because communication is also essential for the developmental stages of children. Through language, they communicate and engage in social interaction. One form of stimulation that can be used to enhance language development in early childhood is social interaction. Therefore, this study aims to investigate the role of social interaction in improving language development in early childhood. The research subjects involved 15 students from TK Negeri Adenium, three of whom exhibited introverted personalities and tended to withdraw from their peers. The research method used included observations and interviews with teachers, as well as direct observation of the students over a certain period. The results of the study showed that social interaction plays a significant role in enhancing language abilities in early childhood.